2019
DOI: 10.1097/mph.0000000000001303
|View full text |Cite
|
Sign up to set email alerts
|

Mucoepidermoid Carcinoma in Warthin Tumor of the Parotis in Childhood: A Case Report and Review of the Literature

Abstract: Mucoepidermoid carcinoma arising in Warthin tumor of the parotid gland is an extremely rare entity. This is so far described only in the adult age group, and only one patient has been reported in the pediatric age group until today. Herein, we describe our patient and review the literature. This was a case of a 9-year-old girl admitted with a painless swelling in the left side of her face for at least 2 weeks. Histopathologic examination of total parotidectomy specimens revealed mucoepidermoid carcinoma arisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
9
0
6
Order By: Relevance
“…Clinically, our data showed that with Warthin-like MEC, there is a slight female preponderance (male to female ratio, 4:5), whereas in other reports on Warthin-like MEC, there was a strong female preponderance. 20,21,23,24,29 For patients with nonsebaceous LAD, the entity was more common in males, which is also different from other reports. 6 In our study, the patients with Warthin-like MEC had a wider age distribution (10-75 years) than the patients with nonsebaceous LAD (47-68 years).…”
Section: Discussionmentioning
confidence: 68%
“…Clinically, our data showed that with Warthin-like MEC, there is a slight female preponderance (male to female ratio, 4:5), whereas in other reports on Warthin-like MEC, there was a strong female preponderance. 20,21,23,24,29 For patients with nonsebaceous LAD, the entity was more common in males, which is also different from other reports. 6 In our study, the patients with Warthin-like MEC had a wider age distribution (10-75 years) than the patients with nonsebaceous LAD (47-68 years).…”
Section: Discussionmentioning
confidence: 68%
“…The tumor has been reported to transform to epithelial and lymphoid malignancies in extreme rare cases. [ 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…The main differential of such types of lesions is the malignant transformation of WT, metaplastic changes in WT and the Warthin-like variant of MEC. The coexistence of WT and MEC is rare, with only 29 cases reported worldwide 4 - 6. Malignant transformation of the epithelial component of WT, such as squamous cell carcinoma, MEC, adenocarcinoma, and undifferentiated, poorly differentiated, and anaplastic carcinoma is extremely rare and only seen in 0.3% of cases 4.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic studies of the tumor showing both WT and MEC characteristics identified specific chromosomal translocations: t(11;19) (q21;p13), and t(11;15)(q21;q26) result in novel fusion oncogenes CRTC1-MAML2 and CRTC3-MAML2 , respectively. These fusion genes act as transcription factors on the Notch and CREB regulatory pathway 6. Ishibashi et al2 reported 15 cases of WT with diffuse squamous metaplasia, 5 of which were reclassified into low-grade MEC after testing positive for CRTC1-MAML2 gene fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation